Expression and Correlation of IgG4 and IL-21 in Collagen-Induced Arthritis Rats - Long ZY (Dove Medical Press, 2021)
Zhen-Yi Long,1,* Yi-Feng Zhou,2,* Hao Yuan,1 Ya-Meng Peng,1 Si-Xian Wu,1 Fang Peng1 1Department of Clinical Laboratory, Hunan Provincial People’s Hospital, The First Affiliated Hospital of Hunan Normal University, Changsha, 410005, People’s Republic of China; 2Operating Room, Hunan Provincial People’s Hospital, The First Affiliated Hospital of Hunan Normal University, Changsha, 410005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hao YuanDepartment of Clinical Laboratory, Hunan Provincial People’s Hospital, The First Affiliated Hospital of Hunan Normal University, Changsha, 410005, People’s Republic of ChinaTel +86-13677366519Fax +86-731-82278012Email yuanhao666@hunnu.edu.cnPurpose: We explored the expression levels of IgG4 and interleukin (IL)-21 in the serum and ankle joints of collagen-induced arthritis (CIA) rats at different disease stages.Materials and Methods: Wistar rats were randomly divided into normal and model groups, and the latter group was administered bovine type II collagen to induce arthritis. Enzyme-linked immunosorbent assay was performed at 21, 28, 35, and 42 days to detect IgG4 and IL-21 in the serum, followed by histological and immunohistochemical analyses of IgG4 and IL-21r in the ankle joint of rats.Results: The contents of IgG4 and IL-21 in the serum of the CIA model group were positively correlated and increased with disease progression. The expression of IgG4 and IL-21 receptors in the ankle joint of the CIA model group was significantly higher than that in the control group. These proteins were closely related to the pathological score. The serum IL-21 level in the model group was closely related to the level of IL-21 receptor in the ankle joint.Conclusion: IL-21 may promote the occurrence and development of rheumatoid arthritis by combining with IL-21r to regulate the content of IgG4.Keywords: rheumatoid arthritis, immunoglobulin, interleukin, interleukin receptor